PENGARUH PENGANGGURAN DAN INFLASI TERHADAP PERTUMBUHAN EKONOMI DI SUMATERA UTARA (Jurnal Kendali Akuntansi, 2023)
Macroeconomics is the study of economic activity in a country. Macroeconomic indicators are inflation, unemployment, and economic growth. The purpose of this study is to see the effect of unemployment and inflation on economic growth in North Sumatra. This study uses the multiple regression method where the data is taken from 1998-2022 per semester. Finally, this study only shows that unemployment has a significant effect on economic growth, while inflation has no significant effect on economic growth.